Strain-Induced Domain Structure and Its Impact on Magnetic and Transport Properties of Gd0.6Ca0.4MnO3 Thin Films - Beiranvand Azar; Rivasto Elmeri; Huhtinen Hannu; Paturi Petriina (AMER CHEMICAL SOC, 2022)
The evolution of lattice strain on crystallographic domain structures and magnetic properties of epitaxial low-bandwidth manganite Gd0.6Ca0.4MnO3 (GCMO) films have been studied with films on different substrates: SrTiO3, (LaAlO3)0.3(Sr2AlTaO6)0.7, SrLaAlO3, and MgO. The X-ray diffraction data reveals that all of the films, except the films on MgO, are epitaxial and have an orthorhombic structure. Cross-sectional dependent microstructural defects. Large-enough tensile strain can increase oxygen vacancies concentration near the interface and can induce vacancies in the substrate. In addition, a second phase was observed in the films with tensile strain. However, compressive strain causes dislocations in the interface and a mosaic domain structure. On the other hand, the magnetic properties of the films, including saturation magnetization, coercive field, and transport property depend systematically on the substrate-induced strain. Based on these results, the choice of appropriate substrate is an important key to obtaining high-quality GCMO film, which can affect the functionality of potential device applications.